The Systematic Literature Review Affective Commitment pada Konteks Asia Tenggara - Pranindy, Jihan (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2024)
The purpose of this Systematic Literature Review (SLR) is to gain an in-depth understanding of the variable Affective Commitment, focusing on its antecedents, consequences, and the research contexts used in studying Affective Commitment. This SLR aims to systematically identify Affective Commitment within the last ten years, limited to Southeast Asian countries. The research methodology involves searching for relevant reference articles that meet eligibility criteria. The search results identified 30 relevant articles to be used as references for compiling the SLR. Each reference article was then identified based on antecedents, consequences, and research contexts related to Affective Commitment. The identification results revealed that the dominant antecedents are Perceived Organizational Support and Transformational Leadership. The consequences of Affective Commitment are predominantly Employee Performance and Turnover Intention. Regarding the research context, most reference articles focus on the employee perspective. With the research focus in Southeast Asian countries, this SLR is expected to serve as a foundational reference for organizations to enhance and sustain Affective Commitment.